Estudio de prefactibilidad para la instalación de una planta productora de pasta de quinua en Arequipa Metropolitana, 2022 - Salas Juanito, Juan Carlo (2022)
The main objective of the research was to determine the pre-feasibility of a quinoa paste production plant in Metropolitan Arequipa, where the market analysis, technical analysis, organizational study, environmental analysis and economic-financial study were carried out. All parts of this research are aimed at defining the product, quinoa flour pasta, a nutritious product with 0% gluten. The research used the survey as a tool for data collection, which helped to delimit the target audience, comprised of 8,318 people with high tendencies to consume quinoa pasta. The project envisions a plant capacity of 282,600 annual packages of quinoa pasta in a 500gr. presentation, which requires 15 sub-processes and 4 operators for the production of pasta. The financial projections determine the economic NPV of the project at S/376,632.01, an IRR of 46.41% and a cost-benefit ratio of 2.23